A Brief Survey Paper on Multi-Legged Robots - Mohammad Behmanesh; Ehsan Amiri Tehranizadeh; Mahmud Iwan Solihin (IAES International Journal of Robotics and Automation (IJRA), 2015)
This paper presents a brief survey on multi-legged robots and their applications in agriculture such as for harvesting. Multi-legged robots have the benefit of more flexibility and adapt to different rough terrain in a better way. They also have very important applications in fulfilling the dangerous tasks such as mine detecting.